A Genetic Variant Ameliorates β-Thalassemia Severity by Epigenetic-Mediated Elevation of Human Fetal Hemoglobin Expression - Chen, Diyu (Am J Hum Genet, 2017)
A delayed fetal-to-adult hemoglobin (Hb) switch ameliorates the severity of β-thalassemia and sickle cell disease. The molecular mechanism underlying the epigenetic dysregulation of the switch is unclear. To explore the potential cis-variants responsible for the Hb switching, we systematically analyzed an 80-kb region spanning the β-globin cluster using capture-based next-generation sequencing of 1142 Chinese β-thalassemia persons and identified 31 fetal hemoglobin (HbF)-associated haplotypes of the selected 28 tag regulatory single-nucleotide polymorphisms (rSNPs) in seven linkage disequilibrium (LD) blocks. A Ly1 antibody reactive (LYAR)-binding motif disruptive rSNP rs368698783 (G/A) from LD block 5 in the proximal promoter of hemoglobin subunit gamma 1 (HBG1) was found to be a significant predictor for β-thalassemia clinical severity by epigenetic-mediated variant-dependent HbF elevation. We found this rSNP accounted for 41.6% of β-hemoglobinopathy individuals as an ameliorating factor in a total of 2,738 individuals from southern China and Thailand. We uncovered that the minor allele of the rSNP triggers the attenuation of LYAR and two repressive epigenetic regulators DNA methyltransferase 3 alpha (DNMT3A) and protein arginine methyltransferase 5 (PRMT5) from the HBG promoters, mediating allele-biased γ-globin elevation by facilitating demethylation of HBG core promoter CpG sites in erythroid progenitor cells from β-thalassemia persons. The present study demonstrates that this common rSNP in the proximal (A)γ-promoter is a major genetic modifier capable of ameliorating the severity of thalassemia major through the epigenetic-mediated regulation of the delayed fetal-to-adult Hb switch and provides potential targets for the treatment of β-hemoglobinopathy.